Analysis of Realistic Mathematics Approach with Ethnomathematics On Students' Mathematical Communication Ability - Dasini, Priya (Holistic Science, 2022)
This study aims to describe the improvement of mathematical communication skills of seventh grade students of SMP Negeri 43 Medan with a realistic mathematics learning approach that is innovated with ethnomathematics. This research is a quantitative research and the population is all class VII, where for class VII-1 as the experimental class and for class VII-2 as the control class, each sample consists of 25 people. From the results of the pre-test data analysis the experimental class is still relatively low with an average value of 52.8 and for the control class it has an average value of 34.4. The results of the post-test data analysis for the experimental class had an increase which obtained an average value of 81.6 and for the post-test class, an average value of 53.2 was obtained. And get the value of x^2 count = 3.864 and x^2 table = 5.991. So, it can be said that all sample groups come from a homogeneous population. From the results of the explanation above, it can be concluded that there is an increase in students' mathematical communication skills with a realistic mathematics learning approach with ethnomathematical nuances